Trivial Excitation Energy Transfer to Carotenoids Is an Unlikely Mechanism for Non-photochemical Quenching in LHCII - Gray, Callum; Wei, Tiejun; Polívka, Tomáš; Daskalakis, Vangelis; Duffy, Christopher D. P. (Frontiers in Plant Science, 2022)
Higher plants defend themselves from bursts of intense light via the mechanism of Non-Photochemical Quenching (NPQ). It involves the Photosystem II (PSII) antenna protein (LHCII) adopting a conformation that favours excitation quenching. In recent years several structural models have suggested that quenching proceeds via energy transfer to the optically forbidden and short-lived S1 states of a carotenoid. It was proposed that this pathway was controlled by subtle changes in the relative orientation of a small number of pigments. However, quantum chemical calculations of S1 properties are not trivial and therefore its energy, oscillator strength and lifetime are treated as rather loose parameters. Moreover, the models were based either on a single LHCII crystal structure or Molecular Dynamics (MD trajectories) about a single minimum. Here we try and address these limitations by parameterizing the vibronic structure and relaxation dynamics of lutein in terms of observable quantities, namely linear absorption (LA) transient absorption (TA) and two-photon excitation (TPE) spectra. We also analyze a number of minima taken from an exhaustive meta-dynamical search of the LHCII potential energy surface. We show that trivial, Coulomb-mediated energy transfer to S1 is an unlikely quenching mechanism. Pigment movements are insufficient to switch the system between quenched and unquenched states. Modulation of S1 energy level as a quenching switch is similarly unlikely. Moreover, the quenching predicted by previous models is likely an artefact of quantum chemical over-estimation of S1 oscillator strength and the real mechanism likely involves non-trivial inter-molecular states.